Semen Quality of Bali Bulls Produced by The South Sulawesi Regional Artificial Insemination Center in The Dry And Rainy Seasons - Adiputra, Kirana Dara Dinanti; Sukandi, Sukandi; Sonjaya, Herry; Hasbi, Hasbi; Suhardi, Suhardi (Fakultas Peternakan Universitas Jambi, 2025)
Background: Bali cattle are one of the most prominent local cattle breeds widely raised by the people of Indonesia. Purpose: This study aimed to investigate the semen quality of Bali cattle produced during the dry and rainy seasons at the South Sulawesi Regional Artificial Insemination Centre (RAIC). Methods: The data of this study were obtained from secondary data from the production records taken by purposive sampling of 5 Bali bulls for 12 months, categorized into the rainy season (May - October 2019) and the dry season (November 2019 - April 2020). The study parameters included semen volume (ml), sperm concentration (10 × 10⁶/ml), sperm motility (%), and post-thawing motility (%). Results: The results indicated that semen volume was not significantly affected by seasonality (P > 0.05). However, sperm concentration, sperm motility, and post-thawing motility were significantly higher during the dry season than in the rainy season (P < 0.05). It can be concluded that the quality of Bali bull semen is superior during the dry season compared to the rainy season. Conclusion: The findings of this study can be applied to the management of Bali cattle breeding, particularly in organizing semen collection schedules and improving reproductive quality through the management of environmental factors and feed.